VersaLaser VL-200. - Snoonian, Deborah (Architectural Record, 2005)
This article focuses on the VersaLaser VL-200 introduced by VersaLaser. Cutting model parts by hand is so 20th century. Leap into the digital age with the VersaLaser VL-200, which uses a computer-controlled laser beam to cut, score, and contour sheets of paper, plastic, wood, fabric, and other materials into any shape you desire. The printer can accept files from many popular drafting and graphics programs, including AutoCAD, Photoshop, and CorelDRAW. Retailing for around $8,000 or leasing for under $200 per month, the VL-200 is less costly than 3D printers used for model making.